SIFAT-SIFAT DAN KEADILAN ALLAH DALAM PEMIKIRAN TEOLOGI MUHAMMADIYAH - Mawangir, Muhammad (JIA (Jurnal Ilmu Agama), 2015)
There are four schools in Islamic theological thought namely, Mu’tazilah, Asyariah, Maturidiah Samarkhand and Maturidiah Bukhara. The four schools can be devided into two types; those are rational and traditional Islamic thought. Mu’tazilah and Maturidiah Samarkand are the rational type; meanwhile Asyariah and Maturidiah Bukhara are traditional type.  The paper try to analyse the theology of Muhammadiyah based on two types of theological thought. Muhammadiyah one of the biggest religious organization in Indonesia, asserts itself as the Islamic puritanist, reformist movement as well. Their comprehension on Allah attributes tends to follow the Asy’ariyah thought that acknowledges the Allah’s attributes. On the other hand, their comprehension on the Allah’s justice tends to follow the thougt of Maturidiyah Samarkan. Allah appraises the men based on their deeds in this world. Thus it can be concluded that on this subject Muhammadiyah has rational theological type.